Hydrogen interaction with a sulfur-vacancy-induced occupied defect state in the electronic band structure of MoS2. Issue 28 (26th April 2019) - Han, Sang Wook; Cha, Gi-Beom; Kim, Kyoo; Hong, Soon Cheol
Abstract : A combination study of photoemission spectroscopy and first-principles calculations reveals that a sufficiently high concentration (2.8–11.1%) of the VS defect on the MoS2 surface induces an occupied defect state in the electronic band structure, in addition to the in-gap defect states. Abstract : Identifying and designing defects are critical steps in the development of a semiconductor. We unveil that a sufficiently high concentration of the sulfur-vacancy defect on the MoS2 surface induces an occupied defect state in the electronic band structures, in addition to the in-gap defect states. The occupied defect state is expected to appear above and below the valence band maximum (VBM) of the mono- and bilayer or bulk band structures of MoS2, respectively. Furthermore, the hydrogen interaction with the sulfur-vacancy defect reconstructs the band structure of MoS2 to have multi VBMs or ambipolar valence bands depending on the layer thickness. Finally, we find that the polarity switching of MoS2 from n-type to p-type conductivity depends on the type of hydrogen bonds at/around the sulfur-vacancy defect.